2017
DOI: 10.5935/2238-3182.20170004
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of overall survival of breast cancer patients in Barbacena, MG

Abstract: Introduction: Breast cancer is the most frequent type of câncer in women, except for cases of non-melanoma skin cancer. It is the fifth cause of cancer death in general and the most common cause of cancer death in women. Survival analysis is intended to keep life expectancy data updated.Objective: To analyze the overall survival of patients with breast cancer in a medium-sized city in the interior of Minas Gerais.Method: A prospective, cross-sectional clinical study was carried out through the analysis of medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 2 publications
0
0
2
1
Order By: Relevance
“…In the multivariate (adjusted) analysis, time to treatment after 60 days, stage IV, and triple-negative classification remained independent prognostic factors. The survival estimates observed in the study were lower than those found in some affluent areas of Brazil [ 22 – 24 ], as well as in high-income countries [ 25 , 26 ] and China (89.4%) [ 27 ].…”
Section: Discussioncontrasting
confidence: 71%
“…In the multivariate (adjusted) analysis, time to treatment after 60 days, stage IV, and triple-negative classification remained independent prognostic factors. The survival estimates observed in the study were lower than those found in some affluent areas of Brazil [ 22 – 24 ], as well as in high-income countries [ 25 , 26 ] and China (89.4%) [ 27 ].…”
Section: Discussioncontrasting
confidence: 71%
“…In the multivariate (adjusted) analysis, time to treatment after 60 days, stage IV, and triple-negative classification remained independent prognostic factors. The survival estimates observed in the study were lower than those found in some affluent areas of Brazil [22][23][24], as well as in highincome countries [25,26] and China (89.4%) [27].…”
Section: Discussioncontrasting
confidence: 76%
“…Foi constatado que 74,4% dos pacientes tiveram acesso ao tratamento por meio do SUS. Estudos mostram que a sobrevida de pacientes que recorrem ao SUS é consideravelmente menor comparadas àquelas que tem acesso ao serviço privado por serem diagnosticadas tardiamente e se encontrarem com maior estadiamento no momento do diagnóstico, além da disparidade na qualidade de tratamento (Alvarenga et al, 2017;Cabral et al, 2019;Guerra et al, 2015). Este estudo demonstrou que o sistema público de saúde diagnosticou cerca de duas vezes menos pacientes no estágio 0-I (15% vs 33%) e duas vezes mais pacientes no estágio III (33% vs 16%) quando comparada à rede privada.…”
Section: Discussionunclassified